'Business Risk-Assumption' as a Criterion for the Determination of EU Employment Status: A Critical Evaluation. (20th January 2021) - Georgiou, Despoina
Abstract: In the European legal order, the criterion of 'business risk-assumption' is increasingly being used by the ECJ as an element that would point to the existence of an independent working relationship. To what type of risks is the Court referring to? What are the normative underpinnings of this criterion and is it still effective in classifying modern-day workers? This paper responds to these questions by analysing and critically evaluating the use of 'business risk-assumption' as a criterion for the determination of EU employment status. More precisely, in section 2, I revisit the classical paradigm that led to the adoption of this criterion and demonstrate how it has been superseded by recent changes in market structures. In section 3, I show why employment status cannot just be left up to the parties and advocate for the need for an alternative 'risk'-based criterion that would mitigate the deficiencies of the current framework, precipitating the fair mutualisation of risks between the parties. Finally, in section 4, I present and critically evaluate alternative 'risk'-related criteria that have been proposed in the literature. After analysing the advantages and disadvantages of each approach, I argue in favour of a classification criterion based on the 'involuntary assumption of risks' measured by the 'inability of a person to spread his risks'. If adopted, the proffered criterion would lead to the expansion of the EU nomen juris of 'worker', allowing for the protection of vulnerable quasi -subordinate persons that are excluded from the current EU 'worker' definition.